2019
DOI: 10.18231/j.ijpca.2019.011
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles used in the antibacterial preparations

Abstract: Nanotechnology is the emerging field in medicine that is expected to induce exceptional therapeutic benefits. Nanoparticles have been improving the therapeutic effect of drugs and are prepared by using varioustechniques. Silver Nanoparticles are attracting interest for the clinical application because of its potential biological properties such as antibacterial properties; antifungal properties etc. Due to its highly efficient properties Silver Nanoparticles are invasively used in the field of medical and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Diterpene (C20) resin acids are the major components of rosin (da Silva Rodrigues-Correˆa et al, 2013). Yadav et al (2014) reported that diterpenoids and triterpenoids are not steam volatile and they are obtained from plants, tree gums and resins. Bhattacharya et al (1989) classified resin under organic binders.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Diterpene (C20) resin acids are the major components of rosin (da Silva Rodrigues-Correˆa et al, 2013). Yadav et al (2014) reported that diterpenoids and triterpenoids are not steam volatile and they are obtained from plants, tree gums and resins. Bhattacharya et al (1989) classified resin under organic binders.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Terpenes are isoprenes of 5 carbons (C 5 H 8 ) n . They present a simple or polymerized molecular structure, and can also present oxygen atoms (called terpenoids), resulting in different chemical functions, such as aldehydes, ketones, alcohols, among others, (Yadav, Yadav & Goyal, 2014).…”
Section: Essential Oil and Plant Extractmentioning
confidence: 99%